ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT EFISIENSI PERBANKAN SYARIAH DENGAN PENDEKATAN DATA ENVELOPMENT ANALYSIS - Miftahurrohman Miftahurrohman (POLITEKNIK LP3I JAKARTA, 2019)
The Purpose of this researche is to analyze of efficiency Islamic Bank of ASEAN Countries and Factors Determining using Data Envelopment Analysis (DEA). Variable used in this research measuring efficiency of Islamic bank is input variable consisting Deposit, Labor Cost, Fixed Asset and output variabel consisting Total of Financing and Operational Income. While the independent variable consists of Capital Adequacy ratio (CAR), Return On Asset (ROA), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Size and Gross Domestic Product (GDP). The results of this research indicate that : 1. The average of Islamic Bank in ASEAN countries have lower efficiency. 2. The Capital Adequacy Ratio (CAR) a significant negative effect to efficiency. 3. Return on Asset (ROA) does not influence on efficiency. 4. Non Performing Financing (NPF) does not influence to Efficiency 5. Financing Deposit Ratio (FDR) a significant positive influence on efficiency. 6. Size does not influence on efficiency. 7. Gross Domestic Product (GDP) is a significant positive influence on Efiiciency.Key words:: Efisiensi Bank, Data Envelopment Analysis (DEA), Return On Asset (ROA), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Size and Gross Domestic Product (GDP)